2012
DOI: 10.5103/kjsb.2012.22.1.043
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Analysis of Lower Extremity Segment dur ing the Fouette en dehors Performed by Ballet Dancers

Abstract: The purpose of this study was to quantitatively examine the biomechanical variables of Fouette turns for expert and beginner ballet dancers and to determine the difference in the variables between the two groups. sixteen female ballet dancers participated in this study.They were divided into an expert group(age, 25.38 ± 1.92 years; height, 168.38 ± 4.66 cm; mass, 49.63 ± 4.41 kg) and a beginner group(age, 20.88 ± 1.13 years; height, 161.63 ± 7.42 cm; mass, 48.88 ± 3.64 kg) depending on their ballet experience.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This indicates that most of the studies on the stability of dancers have been conducted under static conditions. Meanwhile, studies on the dynamic posture of dancers have examined changes in CoM during an arabesque turn motion with and without use of the upper extremities (Park & Kim, 2009) and analyzed lower extremity segments during the Fouette' turn (Lee & Oh, 2012). Another study reported that greater vestibular equilibrium would be associated with rotational motion training (Park & Lim, 2008).…”
Section: Studies On the Balance Ability Of Dancers Have Examined Chanmentioning
confidence: 99%
“…This indicates that most of the studies on the stability of dancers have been conducted under static conditions. Meanwhile, studies on the dynamic posture of dancers have examined changes in CoM during an arabesque turn motion with and without use of the upper extremities (Park & Kim, 2009) and analyzed lower extremity segments during the Fouette' turn (Lee & Oh, 2012). Another study reported that greater vestibular equilibrium would be associated with rotational motion training (Park & Lim, 2008).…”
Section: Studies On the Balance Ability Of Dancers Have Examined Chanmentioning
confidence: 99%
“…If GRF is not utilized properly, people cannot move safely and purposely. When a beginner ballerina pirouettes, they simply spin their bodies without efficiently (Prisk & O'Loughilin, 2008) using vertical force in order to spin, but when an expert pirouettes, they push off of the ground vertically in order to keep themselves spinning for longer (Lee & Oh, 2012;Orendurff, Schoen, Bernatz, Klute, & Glaister, 2008) rather than solely spinning on the balls of their feet. This is an example of utilizing ground reaction force.…”
Section: Introductionmentioning
confidence: 99%